2019
DOI: 10.1002/jsfa.10116
|View full text |Cite
|
Sign up to set email alerts
|

Could squalene be an added value to use olive by‐products?

Abstract: Squalene (SQ) is an intermediate hydrocarbon in the biosynthesis of phytosterols and terpenes in plants.It is widely used for applications such as skin moisturizers, vaccines, or in carriers for active lipophilic molecules. It has commonly been obtained from sharks, but restrictions on their use have created a need to find alternative sources. We present a review of studies concerning SQ in olive groves to characterize its content and to provide new aspects that may increase the circular economy of the olive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 75 publications
(94 reference statements)
2
25
0
1
Order By: Relevance
“…Recently, Martinez–Beamonte et al. [ 13 ] reported a mean value of 4.6 ± 2.1 g kg −1 of VOO with a wide variation from 0.4 to 10.8 g kg −1 . Likewise, the estimated human intake of squalene ranges from 30 up to 400 mg day −1 (in United States and in Mediterranean countries, respectively) [ 14 ] or even 1 g day −1 in some diets.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Martinez–Beamonte et al. [ 13 ] reported a mean value of 4.6 ± 2.1 g kg −1 of VOO with a wide variation from 0.4 to 10.8 g kg −1 . Likewise, the estimated human intake of squalene ranges from 30 up to 400 mg day −1 (in United States and in Mediterranean countries, respectively) [ 14 ] or even 1 g day −1 in some diets.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that squalene has many biological activities, such as anti‐inflammatory, antioxidation antiatherosclerotic, and antineoplastic activities, and can neutralize xenobiotics and is involved in skin aging. It is widely used in the makeup industry as an adjuvant to boost the antigenicity of vaccines and as a carrier for active lipophilic molecules (Martínez‐Beamonte et al, 2019). Squalene is mainly found in shark liver oil, which is also our major source for obtaining it.…”
Section: Resultsmentioning
confidence: 99%
“…Oils in plant seeds and pulp contain many metabolites and are an important source of various nutrients required by the human body, such as fatty acids, sterols, squalene and tocopherol, which possess multiple biological activities (Calder, 2009; Han et al, 2010; Lushchak and Semchuk, 2012; Martínez‐Beamonte et al, 2019). Crops growing in harsh environments tend to accumulate more of the abovementioned metabolites, which are implicated in the activation and reinforcement of defense mechanisms in crops that cope with environmental stress (Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They have also been used for the enrichment of functional olive oils with additional health properties [11]. Other olive-derived compounds associated with health effects include terpenoids such as oleanolic and maslinic acids and biosynthesized intermediate products [12]. Most of the biological effects of these compounds have been tested either collectively [8] or individually [13][14][15].…”
Section: Introductionmentioning
confidence: 99%